2004
DOI: 10.1021/bm049970v
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure of Whey Protein/Gum Arabic Coacervates

Abstract: Complex coacervation in whey protein/gum arabic (WP/GA) mixtures was studied as a function of three main key parameters: pH, initial protein to polysaccharide mixing ratio (Pr:Ps)(ini), and ionic strength. Previous studies had already revealed under which conditions a coacervate phase was obtained. This study is aimed at understanding how these parameters influence the phase separation kinetics, the coacervate composition, and the internal coacervate structure. At a defined (Pr:Ps)(ini), an optimum pH of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(184 citation statements)
references
References 25 publications
11
165
0
Order By: Relevance
“…We have undertaken studies on the phase behaviour of gum Arabic (GA) -bovine serum albumin (BSA) systems by monitoring the turbidity and scattering intensity as the pH was gradually reduced in situ by the slow hydrolysis of glucono delta lactone [38]. For systems containing BSA:GA in ratios between 1:1 and 6:1, the turbidity (monitored by absorbance) was found to increase between pH ~4.7 -5.2 depending on the ratio (Figure 15a).…”
Section: Polysaccharide -Protein Interactionsmentioning
confidence: 99%
“…We have undertaken studies on the phase behaviour of gum Arabic (GA) -bovine serum albumin (BSA) systems by monitoring the turbidity and scattering intensity as the pH was gradually reduced in situ by the slow hydrolysis of glucono delta lactone [38]. For systems containing BSA:GA in ratios between 1:1 and 6:1, the turbidity (monitored by absorbance) was found to increase between pH ~4.7 -5.2 depending on the ratio (Figure 15a).…”
Section: Polysaccharide -Protein Interactionsmentioning
confidence: 99%
“…Protein-polyelectrolyte interactions often leading to coacervation and resulting in biopolymer complexes arises mainly from electrostatic interactions [16]. This complexation is dependent on the ionization degree of these macromolecules and thus the pH.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast during coacervation, the charge neutralization of complexes was achieved through lowering of acacia gum negative charges [8]. Weinbreck et al [9,10,64,65,94] have studied the complex coacervation phenomenon in whey protein and gum arabic solutions and examined the composition and structure of the coacervate phase. The rheological studies revealed the viscous nature of their complex coacervate where G'' dominated over G' .…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity of the coacervate was observed to increase with electrostatic interaction between the two biopolymers. The intermolecular complexes were visualized as gum arabic chains crosslinked by electrostatic interactions with whey protein molecules [9]. Thus, it appears that for each coacervation process there exists signature interaction, rheological behaviour and phase stability road map though some broad observables are common to all.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation